Usefulness of Intravital Multiphoton Microscopy in Visualizing Study of Mouse Cochlea and Volume Changes in the Scala Media - Ju, Hyun Mi; Lee, Sun Hee; Kong, Tae Hoon; Kwon, Seung-Hae; Choi, Jin Sil; Seo, Young Joon (Frontiers in Neurology, 2017)
Currently, no vestibular or auditory diagnostic test is available for endolymphatic hydrops or dilation of the scala media. Clinical diagnosis is based on the physician’s observations and the patient’s history, symptoms, and symptom pattern. By using near-infrared lasers for multi-photon excitation, intravital multi-photon microscopy (MPM) can detect endogenous fluorescence and second harmonic generation of tissues. In this study, we used intravital MPM to visualise various cochlear microstructures without any staining and non-invasively analyse the volume changes of the scala media without removing the overlying cochlear bone. The intravital MPM images revealed various tissue types, ranging from Reissner’s membrane to dense bone, as well as the spiral ganglion beneath the cochlear bone. The two-dimensional cross-sectional and serial z-stack intravital MPM images also revealed the spatial dilation of the scala media in the temporal bone of pendrin-deficient mice. These findings suggest that intravital MPM might serve as a new method for obtaining microanatomical information regarding the cochlea, similar to standard histopathological analyses. Given the capability of intravital MPM for detecting an increase in the volume of the scala media in pendrin-deficient mice, it might be a promising new tool for assessing the pathophysiology of hearing loss.